2023
DOI: 10.1111/cns.14408
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the interaction between microglial adenosine 2A receptor and NLRP3 inflammasome attenuates neuroinflammation posttraumatic brain injury

Abstract: AimsAdenosine 2A receptor (A2AR) is widely expressed in the brain and plays important roles in neuroinflammation, and the nucleotide‐binding oligomerization domain, leucine‐rich repeat, and pyrin domain‐containing protein 3 (NLRP3) inflammasome is a crucial component of the innate immune system while the regulation of A2AR on it in the central nervous system (CNS) has not been clarified.MethodsThe effects of microglial A2AR on NLRP3 inflammasome assembly and activation were investigated in wild‐type, A2AR‐ or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 62 publications
(137 reference statements)
0
1
0
Order By: Relevance
“…The Nod-like receptor protein 3 (NLRP3) inflammasome has emerged as a crucial mediator of neuroinflammation. 13 Upon activation, the NLRP3 inflammasome can activate caspase-1 (casp-1), which in turn cleaves and activates proinflammatory cytokines, leading to the recruitment and activation of immune cells, exacerbating the inflammatory response and promoting tissue damage. 14 In our previous study, we found that NLRP3 can aggravate the degree of CIRI in mice through the activation of inflammasome pathway.…”
Section: Introductionmentioning
confidence: 99%
“…The Nod-like receptor protein 3 (NLRP3) inflammasome has emerged as a crucial mediator of neuroinflammation. 13 Upon activation, the NLRP3 inflammasome can activate caspase-1 (casp-1), which in turn cleaves and activates proinflammatory cytokines, leading to the recruitment and activation of immune cells, exacerbating the inflammatory response and promoting tissue damage. 14 In our previous study, we found that NLRP3 can aggravate the degree of CIRI in mice through the activation of inflammasome pathway.…”
Section: Introductionmentioning
confidence: 99%